1990
DOI: 10.1161/01.str.21.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capsular or thalamic stroke on metabolism in the cortex and cerebellum: a positron tomography study.

Abstract: We used positron emission tomography to study the cortical and cerebellar metabolic rates in 21 strictly selected patients with pure internal capsular infarct (n=8), thalamocapsular hemorrhage (n=6), or pure thalamic stroke (n=7). Significant diffuse ipsilateral cortical hypometabolism relative to 62 controls free of cerebrovascular risk factors was frequently, although not consistently, found in the 13 patients with thalamocapsular or thalamic lesions and neuropsychological impairment but was absent from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0
1

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(60 citation statements)
references
References 28 publications
(31 reference statements)
5
54
0
1
Order By: Relevance
“…Normalized CBF values in the mesial ). Counts in ROIs belonging to the same anatomicofunctional area were averaged, obtaining 11 regions, as follows: basal temporal (T) region (1); basal frontal (F) region (2); lateral temporal cortex (3,7,14); mesial temporal cortex (4); prefrontal region (5,12,16); motor areas (6,13,17,20); parietal (P) cortex (18,21); occipital (O) cortex (8,15,19); caudate nucleus (9); lenticular nucleus (10); and thalamus (11).…”
Section: Resultsmentioning
confidence: 99%
“…Normalized CBF values in the mesial ). Counts in ROIs belonging to the same anatomicofunctional area were averaged, obtaining 11 regions, as follows: basal temporal (T) region (1); basal frontal (F) region (2); lateral temporal cortex (3,7,14); mesial temporal cortex (4); prefrontal region (5,12,16); motor areas (6,13,17,20); parietal (P) cortex (18,21); occipital (O) cortex (8,15,19); caudate nucleus (9); lenticular nucleus (10); and thalamus (11).…”
Section: Resultsmentioning
confidence: 99%
“…Yet a positron emission tomography study on capsular and thalamic strokes suggests that the thalamocortical projections must sustain damage before hypometabolism of the overlying cortical mantle develops. 19 The authors of the same study speculate that cortical hypoactivity per se might suffice to cause a contralateral cerebellar diaschisis. The inverse could have been observed by us; ie, cerebellar deactivation after upper pontine stroke may have back-projected to cortical areas through intact cerebellocerebral connections.…”
Section: Discussionmentioning
confidence: 97%
“…23 ' 6 Interruption of the corticopontocerebellar tracts was, indeed, proposed as an explanation of this remote effect. 1 Nonetheless, the fact that reduced cerebellar metabolism or low flow can be found in strictly thalamic lesions 512 - 13 suggested that a retrograde mechanism or cortical hypometabolism may also play a part. 6 The reduction in hemispheric CBF that we observed had a number of particular features that should be emphasized.…”
Section: Discussionmentioning
confidence: 99%